Trajectory Tracking using LQR Control for Pendubot: Simulation and Experiment - Tran, Trong-Bang; Nguyen, Hoang-Thien; Nguyen, Tay; Dang, Duc-Dat; Pham, Duong-Minh-Quang; Le, Nhat-Duy; Huynh, Hoang-Khuong; Phan, Thanh-Quoc-Du; Nguyen, Bao-Huy; Nguyen, Ngo-Huu-Tung; Pham, Le-Quoc-Toan; Nguyen, Trung-Hieu; Dang, Quang-Vinh (Peneliti Teknologi Teknik Indonesia, 2024)
Pendubot, a unique single-input-multiple-output (SIMO) system, is commonly employed in laboratories to validate control algorithms. In this article, we develop an LQR controller to simulate and assess its effectiveness on this model. Specifically targeting the TOP position for control, we not only verify the controller's quality but also ensure the motion system accurately tracks a predefined trajectory, encompassing sine and square pulses. Control parameters are meticulously chosen through a genetic algorithm (GA). Although LQR is not highly rated for trajectory tracking due to its relatively small operational range, our successful simulations and control of this system are attributed to the assistance of GA